Synthesis, structure and reactivity of the later transition metal complexes containing a multidentate phosphorus-nitrogen hybrid ligand : a dissertation presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Chemistry at Massey University - Kennedy, Steven Michael Fornara (Massey University, 2000)
Chapter 1 - This first part of the chapter aims to give the reader a flavour of the chemistry concerning phosphorus-nitrogen hybrid ligands containing both phosphorus and nitrogen donor atoms. This will be achieved by highlighting selected relevant examples from the literature. The second part will introduce the ligand 2-(diphenylphosphino)-N-[2-(diphenylphoshino)benzylidene]benzeneamine, (PNCHP), which is the subject of Chapters 2 through 6. Chapter 2 - The ligand PNCHP reacts with [Mo(CO)3(1,3,5-cycloheptatriene)] to give the complex fac-[Mo(CO)3(PNCHP-K3 P,N,P)] which readily isomerises to mer-[Mo(CO)3(PNCHP-K3P,N,P)]. Kinetic studies on the isomerisation in acetone yielded the first-order forward rate constants (k1) 1.22x10 -5, 4.18x10 -5, 1.72X10 -4 and 4.89x10 -4 s-1 at 19.5, 29.7, 40.0 and 49.5 °C respectively, with thermodynamic activation parameters ΔH 1‡ and ΔS1‡ of 95 kJ mol-1 and -14.1 J mol-1 K-1 respectively. The related complex fac-[Mo(CO)3(PNHCH2P-K3P,N,P)] (PNHCH2P = 2-(diphenylphosphino)-N-[(2-diphenylphosphino)benzyl]benzeneamine does not undergo isomerisation. The complex cis-[Cr(CO)4(PNCHP-K2N,P)] reacts with sulfur to give cis-[Cr(CO)4(SPNCHP-K2N,P)] and reacts with methyliodide under an atmosphere of carbon monoxide to yield the anion [Cr(CO)5I]-. Chapter 3 - The complexes [M(CO)3(PNCHP-K3P,N,P)] (M = Cr, Mo or W), containing a terdentate PNCHP ligand, react with H+ to give the protonated products [M(CO)3{PN(H)CHP-k2P,P-η2(C=N)}]+, where the imino group has 'slipped' from a K1N to a η2(C=N) coordination mode as a result of the protonation of the nitrogen atom. When the acid is HC1 the above cation [M(CO)3{PN(H)CHP-K2P,P-η2(C=N)}]+ (M = Mo or W) converts to cis-[M(CO)2C12(PNHCH2P-K3P,N,P)]. In this unusual reaction the imine group of the PNCHP ligand has been reduced to an amine concurrently with the two electron oxidation of the metal. In contrast, on reaction of cis-[Cr(CO)4(PNCHP-K2N,P)] with H+, the bidentate PNCHP ligand dissociates from the metal resulting in cyclisation of the ligand to give a phosphonium salt. Chapter 4 - PNCHP favours terdentate coordination with Pd(II) and Pt(II). The complexes [Mcl(PNCHP-K3.P,N,P)]Cl and [Pd(CH3)(PNCHP-K3P,N,P)]Cl are synthesised starting with [MCl2(1,5-cyclooctadiene)] and [M(CH3)Cl(1,5-cyclooctadiene)], respectively. The ionic chlorides can be exchanged with BF4- using AgBF4. Abstraction of the covalent chloride with AgBF4 in the presence of acetonitrile yields [Pt(CH3CN)(PNCHP-K3P,N,P)]2+. The acetonitrile ligand of this dication can be substituted with triphenylphosphane, 2-picoline, or 3-picoline. The reaction of [Pt(CH3CN)(PNCHP-K3P,N,P)]2+. with 1,10-phenanthroline, 2,2'-bipyridine, bis(diphenylphosphino)ethane or 2,2':6',2"-terpyridine (L-L) yields complexes of the type [Pt(L-L)(PNCHP-K3P,N,P)]2+ - the first five-coordinate platinum(II) dications. Chapter 5 - The complex [RhCl(PNCHP-K3P,N,P)] is synthesised by reacting the PNCHP ligand with 0.5 equivalents of [{RhCl(1,5-cyclooctadiene)}2]. This extremely reactive compound undergoes oxidative addition of dichloromethane and chloroform to yield complexes of the type [RhCl2(R)(PNCHP-K3P,N,P)] (R = CH2Cl or CDCl2). Addition of carbon monoxide to [RhCl(PNCHP-K3P,N,P)] results in the adduct [RhCl(CO)(PNCHP-k3P,N,P)] which is in equilibrium with square planar complex [Rh(CO)(PNCHP-K3P,N,P)]Cl. The coordinated chloride ligand of [RhCl(PNCHP-K3P,N,P)] can be substituted with tetrahydrofuran, acetonitrile or triphenylphosphane. Chapter 6 - The triosmium clusters [Os3(CO)11(CH3CN)] and [Os3(CO)10(CH3CN)2] react with PNCHP to give [{Os3(CO)11}2(PNCHP-K2P,P)] (containing PNCHP bridging equatorially two osmium triangles), two coordination isomers of [Os3(CO)11(PNCHP-K1P)] and 1,1-[OS3(CO)10(PNCHP-K2P,P)], respectively. When 1,1-[Os3(CO)10(PNCHP-K2P,P)] is reacted with one equivalent of trimethylamineoxide the major product is [OS3(μ-H)(CO)7(μ3-PNCP)], in which the imine hydrogen of PNCHP has migrated to the osmium cluster and PNCP is left to act as a triply bridging nine-electron donor. Two geometrical isomers of [Os3(μ-H)(CO)8(μ2-PNCP)] are found as minor products, with PNCP acting as a doubly bridging seven-electron donor ligand.
Keywords: Transition metal complexes; Ligands; Chemistry